PERAN DAN PENGARUH YAKUZA DALAM POLITIK DAN PEMERINTAHAN DIJEPANG PASCA PERANG DUNIA II - Harmanita, Ardhisa; Adnan, Muh; H, Priyatno (Journal of Politic and Government Studies, 2014)
and government in Japan , especially after World War II . The designused in writing this paper is a qualitative descriptive method. The data used inthe writting of this paper sourced from written data and unritten data fromvarious data that in the form of secondary data.Yakuza is an organized crimegroup in Japan. Have the organizational structure and embracing family values .Its existence is a paradox because Japan is a country that is well established inthe economy and the level of security . In Japan, the yakuza have a position thatcan not be equated with ordinary criminal actors , such as thugs and so on ,because the yakuza able to form themselves by adopting the values of warrior (samurai ) , was also able to put themselves in the community . But on the otherhand , the yakuza conduct illegal activities such as smuggling unlawful , narcotics, gambling , prostitution , illegal weapons business , financial crime , extortion,money laundering and human trafficking . Legally, of course it is an offense . Butlegal sanctions for the yakuza is not capable enough to be " cleaner " over theexisting that situation.Another fact, yakuza